2009
DOI: 10.1051/epjap/2009073
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and spectroscopy through plasmonic nano-probe

Abstract: Abstract. This article is a comprehensive review of the subject of near-field nano imaging and spectroscopy by surface plasmon polaritons induced on a metallized probe. The emphasis of the review is on fundamental aspects of plasmon enhancement and near-field spectroscopy, which are categorized as optical antenna structures, polarization properties in near-field, resonance frequency of surface plasmons, etc. Most recent studies that contribute to the understanding and interpretation of these phenomena are high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…The second corresponds to the image dipole underneath the metal surface. 66,72 It was found that radially polarized light is more efficient, when illuminating the tip from below, than linear polarized light, because only field components parallel to the tip axis contribute to the signal enhancement. 48,65,73 In Fig.…”
Section: The Ideal Ters Tip: From Modelling To Realizationmentioning
confidence: 99%
“…The second corresponds to the image dipole underneath the metal surface. 66,72 It was found that radially polarized light is more efficient, when illuminating the tip from below, than linear polarized light, because only field components parallel to the tip axis contribute to the signal enhancement. 48,65,73 In Fig.…”
Section: The Ideal Ters Tip: From Modelling To Realizationmentioning
confidence: 99%
“…The plasmonic properties of noble metal nanoparticles (for example, nanospheres composed of gold or silver) have recently been studied and adopted extensively at infrared and optical frequencies because they offer a new range of possible applications, such as the enhancement of Raman spectra [1,2], their use for biosensor devices [3,4], and their potential aptitude to produce artificial magnetism [5][6][7][8][9][10][11]. Furthermore, periodic arrangements of metal nanoparticles present peculiar properties that could be applied to produce enhancement of evanescent fields in subwavelength regions [12][13][14][15][16][17][18], among other innovative applications.…”
Section: Introductionmentioning
confidence: 99%
“…ocalized surface plasmon resonance (LSPR) mediated on a metal particle is of interest because of its ability to confine light and enhance an electric field in nanometric space, 1) and it is the theory behind biosensors, 2) photocatalytic reactions, 3) and high-sensitivity spectroscopic imaging. 4,5) Thus, the properties of LSPR need to be experimentally determined under a variety of conditions. There has been considerable research on the coupling efficiency of fabricated novel nanostructures with LSPR and the incident photon energy.…”
mentioning
confidence: 99%